A fuzzy decision scheme for relay selection in cooperative wireless sensor network. (29th July 2019) - Jain, Nitin Kumar; Yadav, Dharmendra Singh; Verma, Ajay
Summary: In energy‐constrained military wireless sensor networks, minimizing the bit error rate (BER) with little compromise on network lifetime is one of the most challenging issues. This paper presents a new relay selection based on fuzzy logic (RSFL) scheme which provides balance between these parameters. The proposed scheme considers node's residual energy and path loss of the relay‐destination link as the input parameters for the selection of the relay node. The relay node selection by fuzzy logic is based on prioritizing higher residual energy and minimum path loss. To evaluate the performance on wireless sensor network, we compare the proposed scheme with the three existing relay selection strategies, ie, random, maximum residual energy based relay selection (MaxRes), and minimum energy consumption based relay selection (MinEnCon). The simulation results of the proposed scheme in terms of network lifetime, BER, Network Survivability Index (NSI), and average energy of network nodes have been presented and compared with different relay selection schemes. The simulation results show that the proposed RSFL scheme has the lowest BER, moderate network lifetime, average energy, and NSI. Abstract : The proposed relay selection scheme provides a reliable communication and ensure that the destination node received the information while some relay nodes are attacked and destroyed by the enemy troops. The proposed strategy not only minimizes bit error rate (BER) by choosing appropriate path but also maintains high network lifetime for enhance the survivability of the network. Relay nodes do not need to keep the information regarding its neighbour nodes like location and distance. Only destination node keeps the information of all relay nodes because relay selection is performed by the destination node. Proposed scheme shows lowest BER when compared with other existing schemes. And performance of proposed and existing strategies also evaluated on other network parameters, ie, network lifetime, network survivability index (NSI), and average energy of relay nodes.